P fluxes and prokaryotic cycling at benthic boundary layer in the deep southeastern Mediterranean Sea - Sisma-Ventura, Guy; Herut, Barak; Silverman, Bernard W; Katz, Timor; Rubin-Blum, Maxim; Rahav, Eyal (PANGAEA, 2024)
The sediment-water interface is a site of active nutrients exchange between the geosphere and the hydrosphere. We quantified fluxes of dissolved inorganic and organic phosphorous between the deep sediments and the overlying waters of the P-limited southeastern Mediterranean Sea (SEMS) using sediment core incubations. Sediments were collected throughout the Israeli exclusive economic zone and analyzed for their pore-water physicochemical characteristics. We also designed custom-made incubation flux chambers and followed dissolved inorganic and organic phosphorous dynamics as well as prokaryotic microbial activity in the overlying waters for several days. We show that due to the low organic matter content and the well-oxygenated conditions, the sediments of the SEMS function as a PO4 sink. The sedimentary net removal flux of P is equal to a turnover time of ~90 years, similar to the deep water residence time in this basin, hence contributing to the low concentration of PO4 in the deep water of the SEMS. Our incubation experiments show that aside from abiotic processes, such as, adsorption and co-precipitation of PO4, prokaryotic microbial activity play a pivotal role in P-recycling, resulting in a flux of dissolved organic P (DOP) to the overlaying. Organic molecules containing P and C are a known limiting factor for bacteria, and upon release from the sediment stimulated increased prokaryotic microbial activity. Our results highlight the role of the seabed as a hot-spot for microbial activity.
Keywords: deep-sea sediments; DOP; East Mediterranean Sea; P flux; PO4; prokaryotic production.